1997
DOI: 10.1109/43.644030
|View full text |Cite
|
Sign up to set email alerts
|

Explicit and implicit algorithms for binate covering problems

Abstract: We survey techniques for solving binate covering problems, an optimization step often occurring in logic synthesis applications. Standard exact solutions are found with a branchand-bound exhaustive search, made more efficient by bounding away regions of the search space. Standard approaches are said to be explicit because they work on a direct representation of the binate table, usually as a matrix. Recently, covering problems involving large tables have been attacked with implicit techniques. They are based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 28 publications
(57 reference statements)
0
38
0
Order By: Relevance
“…However, this problem is NP-Complete. Villa et al [8] proposed acceleration techniques based on cost bounding. However, even at its best, binate covering can be slow for large CDFGs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this problem is NP-Complete. Villa et al [8] proposed acceleration techniques based on cost bounding. However, even at its best, binate covering can be slow for large CDFGs.…”
Section: Related Workmentioning
confidence: 99%
“…During this procedure it is necessary to remove any overlapping nodesets that arise locally within each set of template matches. Villa et al [8] describe a method of obtaining a close approximation of the maximal independent set using an adjacency matrix, in which the number of nodesets is maximized by first selecting those that conflict with the least number of nodesets, and then eliminating any rows/columns that intersect with a '1'. Expressions with less than two matches are pruned, since there is no benefit to instantiating single-match templates.…”
Section: Template Matching and Selectionmentioning
confidence: 99%
“…(Details of the work on BCP can be found in [4,12,20].) Despite these improvements, and as with other NP-hard problems, additional search pruning ability allows in general very significant gains, both in the amount of search and in the run times.…”
Section: Introductionmentioning
confidence: 99%
“…BCP can be formulated as the problem of finding a satisfying assignment for a given Conjunctive Normal Form (CNF) formula subject to minimizing a given cost function. As with generic Boolean Optimization, BCP also finds many applications, including the computation of minimum-size prime implicants, of interest in Automated Reasoning and Non-Monotonic Reasoning [18], and as a modeling tool in Electronic Design Automation (EDA) [4,20].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, their use is rather limited due to the size explosion problem. It has been observed that so long as the BDD size can be contained, solutions can be found quickly, often with predictable run-times [6] [7] [23]. If, for relatively large hard-to-solve instances, CNF tools invest a large amount of time, and BDDs run into memory explosion, how can their respective capabilities and limitations be leveraged to efficiently search for a SAT solution?…”
Section: ¢ ¤ £mentioning
confidence: 99%